2008
DOI: 10.1001/archopht.126.10.1421
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and Visual Impairment

Abstract: To examine the prevalence and correlates of visual impairment (VI) among US adults with and without diabetes mellitus.Methods: Using National Health and Nutrition Examination Surveys conducted during 1999-2004, we estimated the prevalence of presenting (correctable or uncorrectable), correctable, and uncorrectable VI among Americans 20 years or older with and without diabetes. Data were weighted to make estimates representative of the US civilian noninstitutionalized population. We used multivariate logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 70 publications
4
39
1
1
Order By: Relevance
“…This increase will likely result in increased visual morbidity. The important causes of blindness in subjects with diabetes includes cataract, age-related macular degeneration, glaucoma and uncorrected refractive errors 4. The National Health and Nutrition Survey conducted in the USA reported that VI was more common in diabetics than in non-diabetics 4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase will likely result in increased visual morbidity. The important causes of blindness in subjects with diabetes includes cataract, age-related macular degeneration, glaucoma and uncorrected refractive errors 4. The National Health and Nutrition Survey conducted in the USA reported that VI was more common in diabetics than in non-diabetics 4.…”
Section: Introductionmentioning
confidence: 99%
“…The important causes of blindness in subjects with diabetes includes cataract, age-related macular degeneration, glaucoma and uncorrected refractive errors 4. The National Health and Nutrition Survey conducted in the USA reported that VI was more common in diabetics than in non-diabetics 4. The survey reported that approximately 11% of US adults with diabetes had some form of VI (7.2% correctable and 3.8% uncorrectable).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al 12 18 e as razões cintura/quadril e cintura/ altura, classificadas segundo os pontos de corte correspondentes aos tercis da distribuição.…”
Section: Introductionunclassified
“…2227 Persons with low SEP lack the knowledge and resources necessary to protect themselves against the onset and progression of sensory impairment. 28 They are more likely to develop diseases related to vision impairment 29 or hearing impairment 5,30 and to live and work in noisy environments. 22 They are also less likely to seek eye care and to be aware of the need for such care and more likely to report lack of eye care insurance coverage and cost as barriers to seeking care.…”
mentioning
confidence: 99%